Building and Sustaining National ICT Education Agencies : Lessons from Indonesia (PUSTEKKOM) - Butcher, Neil; Bodrogini, Petra (World Bank, Washington, DC, 2017)
This case study explores the establishment and changing role of Pustekkom, the Centre for Information and Communication Technology (ICT) for Education, which is part of the Ministry of Education and Culture in Indonesia. Originally established a content development house, with a focus on audio and radio and video or film or television content, Pustekkom is currently grappling with a requirement to change its role, given a new mandate that it has been given to plan and provide ICT infrastructure, services, professional development, and resources to schools. Thus, this case study explores the challenges facing Pustekkom, as well as how it is responding to a common challenge facing education systems around the world: how do well established systems and organizations that have operated on a relatively stable set of assumptions for many years cope with the institutional transformation that is being forced on them as growing ICT penetration within societies challenges traditional ways of operating and disrupts entrenched power structures in education? This exploration of a national ICT in education agency with a transforming mandate yields some key lessons of potential relevance globally.